Improvement of regional climate simulation of East Asian summer monsoon by coupled air–sea interaction and large‐scale nudging. (5th May 2015) - Cha, Dong‐Hyun; Jin, Chun‐Sil; Moon, Ji‐Hong; Lee, Dong‐Kyou
ABSTRACT: Impacts of coupled air–sea interaction and large‐scale nudging were examined through regional climate simulation of the East Asian summer monsoon (EASM). A slab ocean model (SOM) was coupled with a regional climate model (RCM) to investigate the impact of two‐way air–sea interaction, and the spectral nudging was applied to examine the effect of large‐scale nudging. The control run without coupled air–sea interaction and large‐scale nudging had significantly large systematic errors in simulated oceanic precipitation, monsoon circulations, and subtropical high. The errors resulted from an erroneous physical process caused by uncoupled air–sea interaction. The experiment with a SOM reduced the unreasonable physical process because simulated sea surface temperature (SST) decreases with enhanced ocean surface mixing from intensified low‐level wind. Therefore, coupled air–sea interaction in the SOM run improved the simulations of seasonal mean precipitation, monsoon circulations, and subtropical high. In the experiment with a SOM and large‐scale nudging, simulated precipitation and synoptic fields were further improved because the spectral nudging decreased the systematic error of large‐scale circulations between model solution and large‐scale forcing. Simulated results indicated that adjusting simulated SST to atmospheric conditions by coupling an ocean model with a RCM and improving boundary conditions by implementing large‐scale nudging are necessary for advanced simulation of the EASM using RCMs.